Career Planning of Higher Secondary School Students - Gautam, Keshab (AJOIS: Academic Journal of Interdisciplinary Studies, 2024)
The research aimed to assess the career planning of higher secondary students. The main focus of the study is concerned with career planning and management of 10 + 2 students under HSEB. Only the respondents are the 10 + 2 students studying in Kathmandu Valley. The survey design adopted by this study appeared to be a successful research attempt. Findings showed similarities of responses among different groups therefore, the findings of the study could be generalized among the respondents. The research revealed that a career is the pattern of job related experiences gained during ones working life. Career planning itself is changing rapidly to respond to dynamic world economy. Career planning is career building in which the emphasis is to help people become healthy, self-reliant citizens able to cope with constant change in rapidly changing labour market and maintain balance between work and life roles.